Advances in three‐dimensional bioprinting of bone: Progress and challenges. (24th April 2019) - Midha, Swati; Dalela, Manu; Sybil, Deborah; Patra, Prabir; Mohanty, Sujata
Abstract: Several attempts have been made to engineer a viable three‐dimensional (3D) bone tissue equivalent using conventional tissue engineering strategies, but with limited clinical success. Using 3D bioprinting technology, scientists have developed functional prototypes of clinically relevant and mechanically robust bone with a functional bone marrow. Although the field is in its infancy, it has shown immense potential in the field of bone tissue engineering by re‐establishing the 3D dynamic micro‐environment of the native bone. Inspite of their in vitro success, maintaining the viability and differentiation potential of such cell‐laden constructs overtime, and their subsequent preclinical testing in terms of stability, mechanical loading, immune responses, and osseointegrative potential still needs to be explored. Progress is slow due to several challenges such as but not limited to the choice of ink used for cell encapsulation, optimal cell source, bioprinting method suitable for replicating the heterogeneous tissues and organs, and so on. Here, we summarize the recent advancements in bioprinting of bone, their limitations, challenges, and strategies for future improvisations. The generated knowledge will provide deep insights on our current understanding of the cellular interactions with the hydrogel matrices and help to unravel new methodologies for facilitating precisely regulated stem cell behaviour.